Laparoscopic and open liver resection for hepatocellular carcinoma with Child–Pugh B cirrhosis: multicentre propensity score-matched study. Issue 2 (6th January 2021) - Troisi, R I; Berardi, G; Morise, Z; Cipriani, F; Ariizumi, S; Sposito, C; Panetta, V; Simonelli, I; Kim, S; Goh, B K P; Kubo, S; Tanaka, S; et al.
Abstract: Background: Laparoscopic liver resection for hepatocellular carcinoma (HCC) in Child–Pugh A cirrhosis has been demonstrated as beneficial. However, the role of laparoscopy in Child–Pugh B cirrhosis is undetermined. The aim of this retrospective cohort study was to compare open and laparoscopic resection for HCC with Child–Pugh B cirrhosis. Methods: Data on liver resections were gathered from 17 centres. A 1 : 1 propensity score matching was performed according to 17 predefined variables. Results: Of 382 available liver resections, 100 laparoscopic and 100 open resections were matched and analysed. The 90-day postoperative mortality rate was similar in open and laparoscopic groups (4.0 versus 2.0 per cent respectively; P = 0.687). Laparoscopy was associated with lower blood loss (median 110 ml versus 400 ml in the open group; P = 0.004), less morbidity (38.0 versus 51.0 per cent respectively; P = 0.041) and fewer major complications (7.0 versus 21.0 per cent; P = 0.010), and ascites was lower on postoperative days 1, 3 and 5. For laparoscopic resections, patients with portal hypertension developed more complications than those without (26 versus 12 per cent respectively; P = 0.002), and patients with a Child–Pugh B9 score had higher morbidity rates than those with B8 and B7 (7 of 8, 10 of 16 and 21 of 76 respectively; P < 0.001). Median hospital stay was 7.5 (range 2–243) days for laparoscopic liver resection and 18 (3–104) days for the open approach ( P = 0.058). The 5-year overall survival rate was 47 per cent for open and 65 per cent for laparoscopic resection ( P = 0.142). The 5-year disease-free survival rate was 32 and 37 per cent respectively ( P = 0.742). Conclusion: Patients without preoperative portal hypertension and Child–Pugh B7 cirrhosis may benefit most from laparoscopic liver surgery. Abstract : Outcomes of laparoscopic liver resection for hepatocellular carcinoma with Child–Pugh B cirrhosis are undetermined. This propensity score matching study demonstrated that laparoscopic resection was associated with reduced blood loss and morbidity, and lower risk of postoperative liver decompensation, leading to shorter hospital stay and with oncological outcomes similar to those of open resection. Benefit when no portal hypertension